3
$\begingroup$

If $n=p_1^{k_1}p_2^{k_2}\cdots p_r^{k_r}$then ,show the inequality :$$ \sigma(n) \phi(n) \geq n^2(1-\frac{1}{p_1^2})(1-\frac{1}{p_2^2})\cdots(1-\frac{1}{p_r^2})$$

I know the function $\sigma(n) \phi(n)$ is multiplicative hence I only have to show the inequality for $n=p^{k}$
So $$\sigma(n) \phi(n)$$ $$\implies \frac{n(p^{k+1}-1)}{p}$$ But after then how to get the desired inequality?

$\endgroup$
  • 1
    $\begingroup$ $n\frac{p^{k + 1} - 1}{p} = n\left( p^k - \frac{1}{p} \right) = n\left( n - \frac{1}{p} \right) = n^2\left( 1 - \frac{1}{np} \right) \geq n^2\left( 1 - \frac{1}{p^2} \right)$ $\endgroup$ – TenaliRaman Jun 16 '12 at 14:33
5
$\begingroup$

Putting $n = p^k$, $\sigma(n)\phi(n) = \frac{p^{k + 1} - 1}{p - 1} p^{k -1}(p - 1) = p^{2k} - p^{k - 1}$ and $n^2 (1 - \frac{1}{p^2}) = p^{2k} - p^{2k - 2}$.

So we get the inequality and furthermore we see that equality happens iff k = 1. Thus for a general $n$ the equality happens iff $n$ is squarefree.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.